2004
DOI: 10.1117/12.559641
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the components of plastic displacement gradients in three dimensions

Abstract: A method for non-destructive characterization of plastic deformation in bulk materials is presented. The method is based on X-ray absorption microtomography investigations using X-rays from a synchrotron source. The method can be applied to materials that contain marker particles, which have an atomic number significantly different from that of the matrix material. Data were acquired at the dedicated microtomography instrument at beamline BW2 at HASYLAB / DESY, for a cylindrical aluminium sample containing W p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A few of these application are presented in this proceeding. 7,[12][13][14][15][16][17] Here the new technique of scanning microtomography to investigate samples larger than the field of view is demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…A few of these application are presented in this proceeding. 7,[12][13][14][15][16][17] Here the new technique of scanning microtomography to investigate samples larger than the field of view is demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…495 Movement of marker particles within metals or in unconsolidated powders can be used very effectively to map displacement fields in response to deformation. [496][497][498][499] Specimens of Al-1 vol.-%Ti (particle diameters between 1 and 10 mm) were imaged with synchrotron microCT at the 2 mm level, and displacement gradients for deformations up to 9?5% compression were quantified. 496,497 Bulk material flow has also been studied in friction stirred welds in Al using the particle technique and synchrotron microCT.…”
Section: Processingmentioning
confidence: 99%
“…[496][497][498][499] Specimens of Al-1 vol.-%Ti (particle diameters between 1 and 10 mm) were imaged with synchrotron microCT at the 2 mm level, and displacement gradients for deformations up to 9?5% compression were quantified. 496,497 Bulk material flow has also been studied in friction stirred welds in Al using the particle technique and synchrotron microCT. 498 Closed die compaction and sintering of powders have long been used to fabricate metal and ceramic components, but constitutive models for loose powder behaviour under intense shear deformation need to be developed.…”
Section: Processingmentioning
confidence: 99%
“…[10][11][12] In the last years, different techniques have been implemented to study displacement and strain fields in the bulk of materials starting from tomograms. Nielsen et al 13 identified several particles in the tomograms at different load stages. In the gray scaled tomograms the gray-value-weighted centers of gravity of each particle were determined, which were used to calculate the displacement gradient tensor of each particle by a least-squares fit of the relative displacement of the eight nearest neighbor particles.…”
Section: Introductionmentioning
confidence: 98%